2003
DOI: 10.1097/00129492-200303000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Furosemide Loading Vestibular Evoked Myogenic Potential for Unilateral Ménière's Disease

Abstract: The F-VEMP test may be useful in the diagnosis of endolymphatic hydrops.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 19 publications
6
35
0
Order By: Relevance
“…As to responses to sternocleidomastoid muscle in ipsilateral monoaural stimulation, we confirmed that the mean of asymmetry rate of patients that presented bilateral responses was 26 8 . In our study, we found one patient (5%) with increase in Vestibular evoked myogenic potentials that presented rate of amplitude asymmetry of 48.2%, suggesting hypersensitivity of saccular macula caused by hydrops of the organ.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…As to responses to sternocleidomastoid muscle in ipsilateral monoaural stimulation, we confirmed that the mean of asymmetry rate of patients that presented bilateral responses was 26 8 . In our study, we found one patient (5%) with increase in Vestibular evoked myogenic potentials that presented rate of amplitude asymmetry of 48.2%, suggesting hypersensitivity of saccular macula caused by hydrops of the organ.…”
Section: Discussionsupporting
confidence: 77%
“…Electrocochleography is not appropriate for the assessment of otolithic organs (sacculus, utriculus and semicircular canals) or descending neural pathways. The determination of saccular hydrops may be useful in the diagnosis of Ménière's disease [4][5][6][7][8] . Vestibular evoked myogenic potentials is a test used to assess sacculocollic reflex in humans, triggered by intensive sound stimulation of saccular macula, which is sensitive to sound even with total destruction of the cochlea 20 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Meniere's disease, the cVEMP is absent in 55% of aVected ears and its absence correlates with low-frequency hearing loss [65].The cVEMP can be augmented in early MD [66], perhaps because the hydropic sacculus presses against the stapes footplate, enhancing saccular sensitivity to loud sound. As the disease advances, cVEMP tends to disappear [67], but can reappear or become enlarged with glycerol or frusemide, drugs which might reduce endolymphatic hydrops [68,69].…”
Section: Clinical Relevance Of Vempmentioning
confidence: 99%